Human pancreatic afferent and efferent nerves: mapping and 3-D illustration of exocrine, endocrine, and adipose innervation - Chien, Hung-Jen; Chiang, Tsai-Chen; Peng, Shih-Jung; Chung, Mei-Hsin; Chou, Ya-Hsien; Lee, Chih-Yuan; Jeng, Yung-Ming; Tien, Yu-Wen; Tang, Shiue-Cheng (American journal of physiology: Gastrointestinal and liver physiology, 2019)
The pancreas consists of both the exocrine (acini and ducts) and endocrine (islets) compartments to participate in and regulate the body’s digestive and metabolic activities. These activities are subjected to neural modulation, but characterization of the human pancreatic afferent and efferent nerves remains difficult because of the lack of three-dimensional (3-D) image data. Here we prepare transparent human donor pancreases for 3-D histology to reveal the pancreatic microstructure, vasculature, and innervation in a global and integrated fashion. The pancreatic neural network consists of the substance P (SP)-positive sensory (afferent) nerves, the vesicular acetylcholine transporter (VAChT)-positive parasympathetic (efferent) nerves, and the tyrosine hydroxylase (TH)-positive sympathetic (efferent) nerves. The SP + afferent nerves were found residing along the basal domain of the interlobular ducts. The VAChT + and TH + efferent nerves were identified at the peri-acinar and perivascular spaces, which follow the blood vessels to the islets. In the intrapancreatic ganglia, the SP + (scattered minority, ~7%) and VAChT + neurons co-localize, suggesting a local afferent-efferent interaction. Compared with the mouse pancreas, the human pancreas differs in 1) the lack of SP + afferent nerves in the islet, 2) the lower ganglionic density, and 3) the obvious presence of VAChT + and TH + nerves around the intralobular adipocytes. The latter implicates the neural influence on the pancreatic steatosis. Overall, our 3-D image data reveal the human pancreatic afferent and efferent innervation patterns and provide the anatomical foundation for future high-definition analyses of neural remodeling in human pancreatic diseases. NEW & NOTEWORTHY Modern three-dimensional (3-D) histology with multiplex optical signals identifies the afferent and efferent innervation patterns of human pancreas, which otherwise cannot be defined with standard histology. Our 3-D image data reveal the unexpected association of sensory and parasympathetic nerves/neurons in the intrapancreatic ganglia and identify the sympathetic and parasympathetic nerve contacts with the infiltrated adipocytes. The multiplex approach offers a new way to characterize the human pancreas in remodeling (e.g., fatty infiltration and duct lesion progression).